Equilibrium and Stability - Allingham, M. G. (Econometrica, 1974)
[This paper presents a model of an economy in which the formation of equilibrium is completely explained by the independent optimizing behavior of individual agents, and thus reformulates the concept of equilibrium in a way which is essentially related to that of stability.]